2018
DOI: 10.1016/j.energy.2018.08.051
|View full text |Cite
|
Sign up to set email alerts
|

Net energy analysis and life cycle energy assessment of electricity supply in Chile: Present status and future scenarios

Abstract: Chile is one of the fastest-growing economies in Latin America, with a mainly fossil fuelled electricity demand and a population projected to surpass 20 million by 2035. Chile is undergoing a transition to renewable energies due to ambitious national targets, namely to generate 60% of its electricity from local renewable energy by 2035, and to achieve a 45%renewable energy share for all new electric installed capacity. In this work, we present a comprehensive energy analysis of the electricity generation techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…Net Energy Analysis (NEA) provides a different and complementary viewpoint to LCA [23,26,28,29,76], and it is carried out here using the same underlying inventory analysis, thereby providing an internally coherent platform for the calculation and discussion of the results. Specifically, while LCA draws the boundary of the system under analysis so as to account for all natural resources used as inputs (and all emissions to the environment as outputs), NEA is only concerned with those energy inputs that are already available as energy carriers within the technosphere, and which are deliberately "invested" in the system (Inv) for the purpose of harvesting more primary energy (PE) from nature and delivering (the term "returning" is also often used) a usable energy carrier (EC) to society.…”
Section: Net Energy Analysis (Nea)mentioning
confidence: 99%
See 1 more Smart Citation
“…Net Energy Analysis (NEA) provides a different and complementary viewpoint to LCA [23,26,28,29,76], and it is carried out here using the same underlying inventory analysis, thereby providing an internally coherent platform for the calculation and discussion of the results. Specifically, while LCA draws the boundary of the system under analysis so as to account for all natural resources used as inputs (and all emissions to the environment as outputs), NEA is only concerned with those energy inputs that are already available as energy carriers within the technosphere, and which are deliberately "invested" in the system (Inv) for the purpose of harvesting more primary energy (PE) from nature and delivering (the term "returning" is also often used) a usable energy carrier (EC) to society.…”
Section: Net Energy Analysis (Nea)mentioning
confidence: 99%
“…To this date, however, literature is divided as to this important question, with some studies questioning the capability of future renewable-heavy grid mixes to deliver sufficient net energy (e.g., for the case of Australia [27]), and others instead concluding that the net energy set-backs could be minor (e.g., for New York state [28]) to non-existent (e.g., for Chile [29]). Ultimately, the devil is, once again, in the details, and the answer is likely to depend on specific conditions such as the exact grid mix composition, location, degree of gird-level storage, and the demand profile.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ensuing issue about consistency in EROI comparisons has often been summarily addressed by simply adjusting the EROI of electricity upwards (or, correspondingly, that of thermal fuels downwards) using power plant conversion efficiencies 8,11,12 . But recent detailed analyses 13,14 have shown that this approach is too simplistic, since it fails to take into account the often significant additional energy investments that are required to refine and/or transport the fuels from their respective extraction points to the power plants.…”
Section: System Boundariesmentioning
confidence: 99%
“…Similarly significant reductions in EROI along the supply chain, from point of extraction to point of use, apply to many other thermal energy resources too, although the relative importance of the energy required for refining / processing (Invref) and for transportation (Invtr) may be reversed. For instance, in three recent studies, the EROI of coal was found to be reduced from 27 (EROIst) to 11 (EROIpou) for the UK supply chain 13 , from 42 (EROIst) to 26 (EROIpou) for the Indonesian supply chain 19 , and from 65 (EROIst) to 20 (EROIpou) for the Chilean supply chain 14 . In all these cases, the main factor responsible for the reductions was Invtr.…”
Section: Oil and Coal Supply Chainsmentioning
confidence: 99%
“…It is also worth noting that it is important to assess each electricity grid as a whole, including all the electricity generation, transmission and storage technologies, and estimate the associated overall environmental impacts and energy implications, as discussed in some recent studies [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%